Polymorphs of the Gadolinite‐Type Borates ZrB2O5 and HfB2O5 Under Extreme Pressure - Pakhomova, Anna; Fuchs, Birgit; Dubrovinsky, Leonid S.; Dubrovinskaia, Natalia; Huppertz, Hubert (Chemistry : a European journal, 2021)
Based on the results from previous high‐pressure experiments on the gadolinite‐type mineral datolite, CaBSiO4(OH), the behavior of the isostructural borates β‐HfB2O5 and β‐ZrB2O5 have been studied by synchrotron‐based in situ high‐pressure single‐crystal X‐ray diffraction experiments. On compression to 120 GPa, both borate layer‐structures are preserved. Additionally, at ≈114 GPa, the formation of a second phase can be observed in both compounds. The new high‐pressure modification γ‐ZrB2O5 features a rearrangement of the corner‐sharing BO4 tetrahedra, while still maintaining the four‐ and eight‐membered rings. The new phase γ‐HfB2O5 contains ten‐membered rings including the rare structural motif of edge‐sharing BO4 tetrahedra with exceptionally short B−O and B⋅⋅⋅B distances. For both structures, unusually high coordination numbers are found for the transition metal cations, with ninefold coordinated Hf4+, and tenfold coordinated Zr4+, respectively. These findings remarkably show the potential of cold compression as a low‐energy pathway to discover metastable structures that exhibit new coordinations and structural motifs. Push the boundaries: The behavior of β‐HfB2O5 and β‐ZrB2O5 under extreme pressure up to 120 GPa has been studied by synchrotron‐based in situ high‐pressure X‐ray diffraction in a diamond anvil cell. Both compounds remain stable to the highest applied pressure and for both experiments, a second additional phase, named γ‐HfB2O5 and γ‐ZrB2O5, respectively, was found at pressures above 114 GPa.